Age-Specific Transmissibility Change of COVID-19 and Associations With Breathing Air Volume, Preexisting Immunity, and Government Response - Song, Qifa; Cao, Chao; Xiang, Yi; Ruan, Liemin; Qian, Guoqing (Frontiers in Public Health, 2022)
Background: The comprehensive impacts of diverse breathing air volumes and preexisting immunity on the host susceptibility to and transmission of COVID-19 at various pandemic stages have not been investigated. Methods: We classified the US weekly COVID-19 data into 0–4, 5–11, 12–17, 18–64, and 65+ age groups and applied the odds ratio (OR) of incidence between one age group and the 18–64 age group to delineate the transmissibility change. Results: The changes of incidence ORs between May, 2020 and November, 2021 were 0.22–0.66 (0–4 years), 0.20–1.34 (5–11 years), 0.39–1.04 (12–17 years), and 0.82–0.73 (65+ years). The changes could be explained by age-specific preexisting immunity including previous infection and vaccination, as well as volumes of breathing air. At the early pandemic, the ratio that 0–4-year children exhaled one-fifth of air and discharge a similar ratio of viruses was closely associated with incidence OR between two age groups. While, after a rollout of pandemic and vaccination, the much less increased preexisting immunity in children resulted in rapidly increased OR of incidence. The ARIMA model predicted the largest increase of relative transmissibility in 6 coming months in 5–11-year children. Conclusions: The volume of breathing air may be a notable factor contributing to the infectivity of COVID-19 among different age groups of patients. This factor and the varied preexisting greatly shape the transmission of COVID-19 at different periods of pandemic among different age groups of people.